TINJAUAN HUKUM TANGGUNG JAWAB PENGELOLA ATAS KEJAHATAN DI MALL - Sundari, Sundari (Faculty of Law, University of Palembang, 2021)
The establishment of a modern shopping center in Indonesia that has great potential to attract attention to people who like to shop. In addition, as a center of the crowd, the mall has a huge potential for crime. The study aims to legally review how managers are responsible for crimes on the Mall. The research method used in this study is a normative method of law. The results of this study are First, before deciding to file a PMH lawsuit against the mall manager, it is advisable to consider carefully the amount of compensation compared to all the time, energy, and costs that may arise from filing the lawsuit. Second, even if the aggrieved party does not ask for damages to the mall manager through the PMH lawsuit, you still have the right to ask for the damages, because the article 1365 of the Civil Code states that the obligation to pay damages arises when the unlawful act causes harm, not when there is a court ruling.